(untitled) (The Review of Diabetic Studies, 2025)
This study aims to describe the current reality of dealing with emergency reports involving multiple injuries in the Kingdom of Saudi Arabia The study adopts a descriptive research approach to present an objective picture of the procedures coordination mechanisms and response practices followed by emergency medical services when handling incidents that involve more than one injured person The focus is on reviewing existing practices as documented in previous studies official reports and relevant research related to emergency response systems The study relies on analyzing available literature to describe how emergency reports are received classified and managed as well as how resources are mobilized and coordinated among different emergency agencies Attention is given to identifying common challenges highlighted in earlier studies such as response time communication efficiency availability of trained personnel and adequacy of equipment during multiple-injury incidents By comparing findings across related research the study provides a comprehensive descriptive overview of the current situation without applying experimental or analytical interventions The results are expected to contribute to a clearer understanding of strengths and gaps in dealing with emergency reports of multiple injuries thereby supporting future planning and improvement efforts in emergency medical services in the Kingdom of Saudi Arabia